ANALISIS TANGGUNGJAWAB PENYIDIK POLRI DALAM KASUS SALAH TANGKAP (ERROR IN PERSONA) TERHADAP TERSANGKA PELAKU TINDAK PIDANA - Wibowo, Teguh Reksoarto; Pello, Jimmy; Amalo, Heryanto (Petitum Law Journal, 2023)
The arrest process carried out by National Police investigators against suspects who are strongly suspected of having committed a criminal act may experience errors or mistakes that originate from human error, namely errors made by investigators in practice in the field. Mistakes in the arrest process have quite big consequences because if these mistakes are not immediately corrected they will continue in the following stages. The aim of this research is to find out what the responsibilities of a National Police investigator are and the legal measures that can be taken by victims of wrongful arrest.The research method used is a Normative law research method where the researcher obtains data via the internet and processes the data in the IMAM CHAMBALI Supreme Court Decision No. 89 PK/PID/2008. The data collection technique uses a case approach and literature study in the form of books, statutory regulations and other materials related to the problem being studied. Data analysis uses qualitative data analysis. The results of this research show that: First, The responsibility of POLRI investigators in the event of an error in person based on the Indonesian Criminal Procedure Law system is contained in Law no. 2 of 2002 concerning the National Police of the Republic of Indonesia and the Code of Professional Ethics for the Police of the Republic of Indonesia in the National Police Chief Regulation no. Pol. : 7 of 2006. Second, the legal remedies that can be taken in the event of an error in person by POLRI investigators based on the Indonesian Criminal Procedure Law system are in the form of compensation, rehabilitation and extraordinary legal remedies, namely judicial review. A convict who is serving a sentence from a decision that has legal force still has the opportunity to take extraordinary legal action, namely a judicial review.